CHINA’S «ONE BELT, ONE ROAD» (OBOR) INITIATIVE: WHAT A DIFFERENCE D «BRAND» CAN MAKE - M. H. Glantz (Проблемы постсоветского пространства)
This paper is about branding goods and services and viewing China’s reference to OBOR, a new regional trade initiative, as the “accidental” branding of its efforts to institute an entirely new model of development in various places along the ancient Silk Road, as well as a number of places that fall under Chinese contemporary rise to dominance in Asia. President Xi’s use of the Silk Road was meant to generate nostalgia about a perceived favorable time in Chinese history, using it to encourage enthusiasm about China’s new efforts to “share or sell” its expertise and heavy industrial production, such as infrastructure, to developing areas. However, in a very short time Xi’s “One Belt, One Road” policy, referred to by its initials — OBOR, began to exhibit most if not all, the characteristics of a “Brand” name for goods and services.OBOR elicited positive comments from national political leaders, all of whom were potential OBOR consumers. In short order, OBOR has attracted attention, interest, responses and offers of cooperation not only from Eurasian leaders but also from leaders in Africa, Europe, Asia and most recently in South America. Strengthening OBOR as a brand can help China to enhance the value of its OBOR-related goods and services internationally and eventually lead to China’s ultimate ascendance as a dominant World economic and political Power.It is interesting to note that a new Silk Road initiative was considered by the US Department of State in 2011 in an attempt to promote integration in trade and economy between Afghanistan, Central Asia, Pakistan, and India, a North-South silk road “as a compliment to the East-West connection across Eurasia” (US State Department 2015). As noted by in a Council on Foreign Relations report by McBride (2015): «It remains to be seen if the United States and China will clash over their competing plans for developing resources in Central Asia’s Turkmenistan, creating infrastructure in Pakistan, or winning political influence with local governments throughout Asia».